PENGARUH SERTIFIKASI DAN KOMITMEN TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA PADA SDN GUGUS I BALIKPAPAN SELATAN - Faridah Faridah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This research is to know the effect of certification on work performance and motivation of teacher, influence of commitment to teacher performance and teacher work motivation, influence work motivation to teacher performance, influence of certification to teacher performance through work motivation and influence of commitment to teacher performance through teacher work motivation SDN Segugus 1 South Balikpapan. This research uses quantitative approach and explanatory research type. The population in this study is all teachers at SDN Segugus 1 South Balikpapan. The sample of this study amounted to 58 teachers. Sampling technique using purposive sampling. Methods of data collection using questionnaires and documentation. Methods of data analysis used descriptive analysis and path analysis. The results showed that certification had a significant effect on teacher performance and motivation in SDN Segugus 1 South Balikpapan. Commitment has a significant effect on teacher performance and motivation at SDN Segugus 1 South Balikpapan. Motivation of work has a significant effect on teacher performance at SDN Segugus 1 South Balikpapan. Certification has a significant effect on teacher performance at SDN Segugus 1 South Balikpapan through work motivation. Commitment has a significant effect on teacher performance at SDN Segugus 1 South Balikpapan through work motivation.